A Study of the Concept of Pluralism (Al-Qamar, 2021)
Pluralism opens the way for actual and different religious commitments. A few people express and opinion that pluralism definitely waters down an individual’s own doctrinal ideology by way of acknowledging that rest of others have faith in differently. Aside from this, a few wrongly think that a pluralistic position points out to develop no real diversity between many religious cultures, traditions and their principles. Besides this, a pluralist culture or society is a hub of encounters actual commitments as well as original differences. The great kingdoms and empires have face up to this reality. Muslims have also confronted this phenomenon at the time of their rule in various parts of the world.
Keywords: Pluralism; Religious; ideology; differences; society; phenomenon